Diabetes insipidus after suprasellar tumor surgery: case report - Yuriz Bakhtiar; Muhamad Thohar Arifin; Adrian Pratama; Jacob Bunyamin (DiscoverSys Inc., 2020)
Introduction: Diabetes insipidus (DI) is a rare water and electrolyte imbalance with hypovolemic hypernatremia characteristic (1:25.000) however can be potentially fatal if not well-anticipated and managed adequately. Brain tumors, either operated or not, may lead to DI (25%). Based on anatomical location, the suprasellar tumor may cause hypophyseal hormone dysfunction. Sellar region tumors can be classified into hypophyseal (90%) and non-hypophyseal (10%). Non-hypophyseal tumors with neurological deficits are more often causing hypophyseal hormone hyposecretion including DI. Sellar tubercle meningioma is one of the sellar region non-hypophyseal tumors which is often encountered and surgically managed. Worsening symptoms may become the surgical indication e.g. headache and visual disturbance.Â Case: We are reporting two meningioma cases in Salatiga local hospital with almost similar tumor characteristics either size and frontal lobe location. Both cases were managed by similar transcranial tumor excision craniotomy. Their differences were in the presence of neurological manifestations and the degree of hypothalamic compression. One patient developed postoperative DI without thirst thus the clinical manifestation was polyuria which was closely monitored in the intensive ward. We were convinced that the DI incidence was affected by the tumor manifestation and location which can be assessed by computed tomography (CT) scans. Conclusion: The clinicians should anticipate the possibility of post craniotomy DI thus may provide adequate monitoring and management in patients developing postoperative DI.